Clinical Presentation of Migraine Patients in a Headache Clinic of a Tertiary Care Hospital in Chattogram (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Migraine is a common cause of medical consultation, both in primary care and in specialist neurology outpatient clinics. This study analyzed the characteristics of migraine patients during a 6-month period in a tertiary care headache outpatient clinic.Materials and methods: This cross-sectional study was conducted in the Department of Neurology, Chittagong Medical College Hospital, Chattogram. Clinically diagnosed cases of migraine in accordance with the International Headache Classification, ranging from 15 years onwards, irrespective of sexes were the study population. A total of 50 migraine patients who met the eligibility crite- ria were include in the study as sample. Sociodemographic and data on clinical profile were collected as per a predesigned case record form.Results: Majority of the patients was in 20-30 years of age group and female preponderance was noticed with a female to male ratio of 3:1. The patients were predominantly lower class (58%) married (82%) and urban resident (90%). Among the comorbidities, psychiatric problems like depression and anxiety was present in 16% and 14% participants respectively. Other comorbidities were obesity (18%) hypertension (4%) and diabetes (6%). Migraine without aura (78%) was more common than migraine with aura (22%). Pain mostly was of moderate severity and each episode lasted for an average of 25 hours. Majority complained nausea (90%) photophobia (84%) and vertigo (76%). The attack was primarily precipitated journey (50%) loud noise (36%) and physical exertion (30%). Pain was invariably relieved by taking analgesics, rest and adequate sleep. Only 4% patients reported hospitalization for their previous attack.    Conclusions: Migraine is a chronic disabilitating disorder. In this study we focused on symptoms of migraneous population, clinical presentation among respondents of this study showed most of female were more affected, mostly were married and lived in urban area. Future community based study is recommended in order to generalize the findings.JCMCTA 2020 ; 31 (2) : 59-64